Protection of Human Rights under the European Convention on Human Rights in Central Europe: Bosnia and Herzegovina - Krešić, Boris (European Integration Studies, 2025)
According to the Constitution of Bosnia and Herzegovina (BiH; Annex 4 to the General Framework Agreement for Peace in BiH), the state of BiH is defined as a democratic and legal state with free and democratic elections. By signing the Dayton Peace Agreement and accepting the Constitution, BiH undertook to ensure the highest level of internationally recognised human rights and fundamental freedoms. Thus, the European Convention for the Protection of Human Rights and Fundamental Freedoms (better known as the European Convention on Human Rights − ECHR) received a special status in the Constitution of BiH. Similar to other modern democratic and legal states, BiH has signed all the other international and regional instruments for the protection of human rights. Therefore, by insisting on the protection of human rights, it was necessary for all people in BiH, as well as in other democratic and legal states, to have an equal status towards the state and the government, which would ensure measures to overcome antagonisms created on the basis of religious, ethnic, racial, and national diversity in BiH. Political participation in BiH needs to be viewed as a broader phenomenon that includes not only elections as the basis of democracy and a prerequisite for effective and legitimate decision-making, but also the participation of citizens in everyday political events and life. Furthermore, political participation in a state is limited by ethnicity and territorial origin. This means that only constituent peoples, as guaranteed by the Constitution and numerous laws, are allowed to run for the three-member Presidency of the State or the House of Peoples of BiH. National minorities are excluded from these branches of government, and their political participation is limited solely to local levels of legislative power. Although BiH, according to the Constitution, is considered a democratic state, it is unable to protect the rights of all its citizens and fulfil their basic human rights guaranteed by numerous internationally recognised conventions, but primarily by the ECHR.